Exploring Parent-Based Health Promotion Models For The Prevention Of Sexual Violence Against Children In Bekasi City: An Exploratory Sequential Mixed Study - Handayani, Handayani; Lail, Nurul Husnul (Journal of Applied Nursing and Health, 2025)
Background: Child sexual abuse (CSA) is a serious problem that continues to increase and is often perpetrated by people close to the child, making it difficult to detect. It has a long-term impact on child development. However, systematically tested parent-based interventions are still limited, especially in Indonesia. This study aims to develop and evaluate a parent-based health promotion model to prevent CSA in Bekasi City.. Methods: This study used a sequential exploratory mixed methods design in accordance with GRAMMS guidelines. The qualitative stage involved in-depth interviews with 12 informants (perpetrators, parents of victims, and child victims of KSPA) which were analyzed thematically. The quantitative stage used a cross-sectional design with 209 respondents selected through proportional sampling in each sub-district and simple random sampling. The inclusion criteria were parents with children aged 6–13 years, cooperative, residing in Bekasi, and willing to be respondents. The data were analyzed using multivariate logistic regression (p-value) and paired samples test. Results: Qualitative analysis identified three main themes: children's vulnerability due to lack of early sex education, permissive parenting, and parental adaptive strategies. The Handayani model identified perpetrator, child, and parental factors that influence KSPA prevention. Quantitative analysis showed that parenting (p<0.001), attitudes, perceptions, and knowledge (p<0.01) were significant. The paired samples test confirmed an increase in all variables after the intervention (p<0.001). The Handayani model proved effective as a guide for parents in improving KSPA prevention through parenting, attitudes, perceptions, and knowledge.. Conclusion: The Handayani model has been proven effective in improving parenting, attitudes, perceptions, and knowledge of parents, so that children are more aware of predators. These findings emphasize the importance of early sex education and protective parenting in family-based prevention programs